PENERAPAN STRATEGI PEMBELAJARAN AKTIF (ACTIVE LEARNING STRATEGY) DALAM MENGANGKAT PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM - Heriadi Heriadi; Rudy liklik watil (Bajang Institute, 2023)
In everyday problems, the problem faced is how the educator (religious teacher) can carry out his duties properly, because lately many students are still lacking in understanding the teachings of Islam. Is this due to students who are still less active in following the teaching and learning process or the teacher's way of teaching is monotonous, so students become apathetic. Therefore, teachers must choose the right method, namely by using active learning strategies where active learning has a lot of learning methods to activate students in learning in class and outside the classroom. The problems to be discussed in this study are: how to apply an active learning strategy in learning Islamic religious education at SDI Nurul Hidayah and what are the inhibiting and supporting factors for the application of an active learning strategy in learning Islamic religious education at SDI Nurul Hidayah. In this study, the author used qualitative methods, with data collection techniques through observation, interviews and interviews, and documentation. As for writing data, a qualitative descriptive method is used, where the description is explained on the visible symptoms. Based on the results of the study that the application of an active learning strategy in the learning process of Islamic religious education at SDI Nurul Hidayah went well, although there were still shortcomings. Among the methods used in learning Islamic education at SDI Nurul Hidayah which leads to an active learning approach. (active learning strategy) is a method of recitation, discussion, problem solving, jigsaw. index card match, drill exercise. Q&A, role-playing and demonstrations. The supporting factors in learning Islamic religious education are the high interest of students in learning, the existence of adequate learning facilities and resources for the learning process, while the inhibiting factors in the application are the existence of some students who are reluctant to express their opinions, and different student backgrounds.